The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ma16093494
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Model Verification of the Stress-Strain State of Reinforced Polymer Concrete

Abstract: This article considers the prospects of the application of building structures made of polymer concrete composites on the basis of strength analysis. The issues of application and structure of polymer-concrete mixtures are considered. Features of the stress-strain state of normal sections of polymer concrete beams are revealed. The dependence between the stresses and relative deformations of rubber polymer concretes and beams containing reinforcement frame and fiber reinforcement has been determined. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Kim [49] highlighted the latest breakthroughs in cement and concrete research, including novel strategies for lowering carbon dioxide emissions in Portland cement production, such as the development of new building materials [50], and the development of mathematical modeling of the reliability of new composite materials [51]. Furthermore, it is necessary to highlight the importance of the prediction of the performance properties and reliability of new building materials [52]. For instance, AL-Kharabsheh et al [50] suggested the partial replacement of Portland cement clinker in cement with wooden ash and studied its effect on concrete compressive strength and durability, concluding that 10% is the optimum replacement.…”
Section: Methods To Estimate the Carbon Dioxide Removals Due To Carbo...mentioning
confidence: 99%
“…Kim [49] highlighted the latest breakthroughs in cement and concrete research, including novel strategies for lowering carbon dioxide emissions in Portland cement production, such as the development of new building materials [50], and the development of mathematical modeling of the reliability of new composite materials [51]. Furthermore, it is necessary to highlight the importance of the prediction of the performance properties and reliability of new building materials [52]. For instance, AL-Kharabsheh et al [50] suggested the partial replacement of Portland cement clinker in cement with wooden ash and studied its effect on concrete compressive strength and durability, concluding that 10% is the optimum replacement.…”
Section: Methods To Estimate the Carbon Dioxide Removals Due To Carbo...mentioning
confidence: 99%
“…ABS, concrete, and aluminum are widely used materials in industries, such as automotive, construction, and aerospace. Understanding crack propagation in these materials is of practical significance for ensuring the reliability and durability of structures made from them [16][17][18][19][20][21][22][23]. By evaluating the performance of machine learning models on these materials, the study can provide insights and guidance for real-world applications, aiding in the design and maintenance of structures involving ABS, concrete, and aluminum.…”
Section: Specimen Parameters and Experimental Data Collectionmentioning
confidence: 99%
“…Autonomous systems used to be the most popular solution among these systems [7]. They were created to provide electricity to places where no other energy sources were available.…”
Section: Introductionmentioning
confidence: 99%